2006
DOI: 10.1007/s11136-006-9136-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the initial Brazilian version of the CHQ-PF50 applied to the caregivers of children and adolescents with cerebral palsy

Abstract: The initial Brazilian version of the CHQ-PF50 showed, in general, adequate psychometric properties for application in patients with CP. Although floor and ceiling effects are expected in heterogeneous group as a limitation inherent to generic assessment instruments, they must be carefully considered in further studies. The general health perception and role/social limitations-emotional behavioral scale must be further reviewed for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 24 publications
4
18
0
11
Order By: Relevance
“…27,30,31 This result may suggest issues with the cultural adaptation of this instrument or difficulty in understanding items of the scale.…”
Section: Discussionmentioning
confidence: 99%
“…27,30,31 This result may suggest issues with the cultural adaptation of this instrument or difficulty in understanding items of the scale.…”
Section: Discussionmentioning
confidence: 99%
“…Our study evaluated the QL of the mothers of children with microcephaly due to the increasing number of cases in Brazil and in other countries, and the impact that the disease causes on the life of these mothers. Previous studies have evaluated the QL of parents or caretakers of children with developmental disabilities or disorders such as autism, Down's syndrome and cerebral palsy [6,10,11], but no studies on the QL of the mothers of children with microcephaly were found.…”
Section: Resultsmentioning
confidence: 99%
“…At the time of the study implementation, no other generic HRQoL questionnaire validated in Brazilian fulfilled all these requirements. The CHQ-PF50 (parent form) [18,20] could have been added as a concurrent measure to explore the convergent validity of the instruments. However, this would have well complicated the study design since parents' reports should have been collected in addition to adolescents' ones and was likely to jeopardize the study carrying-out.…”
Section: Discussionmentioning
confidence: 99%
“…The Child Health Questionnaire (CHQ) [18,20] was modeled after the SF-36 to survey health status in the Medical Outcomes Study. The child self-report version of the CHQ consists of 87 items, and was developed for children from 10 years of age; a version that can be completed by the parent is available in 2 lengths - 50 or 28 items [21,22].…”
Section: Introductionmentioning
confidence: 99%